Pencerahan Kronologi Pameran Still (A) Live - Paiman, Noor Azizan Rahman; Mohd Aripin, Nur Adibah Nadiah; Matrahah, Izaddin (Idealogy Journal, 2019)
Letter to Editor - No Abstract Abstrak Pandangan - tiada abstrak